Supporting health promotion practitioners to undertake evaluation for program development - Lobo, Roanna; Petrich, Mark; Burns, Sharyn (BioMed Central Ltd, 2014)
BackgroundThe vital role of evaluation as integral to program planning and program development is well supported in the literature, yet we find little evidence of this in health promotion practice. Evaluation is often a requirement for organisations supported by public funds, and is duly undertaken, however the quality, comprehensiveness and use of evaluation findings are lacking. Practitioner peer-reviewed publications presenting evaluation work are also limited. There are few published examples where evaluation is conducted as part of a comprehensive program planning process or where evaluation findings are used for program development in order to improve health promotion practice. DiscussionFor even the smallest of programs, there is a diverse array of evaluation that is possible before, during and after program implementation. Some types of evaluation are less prevalent than others. Data that are easy to collect or that are required for compliance purposes are common. Data related to how and why programs work which could be used to refine and improve programs are less commonly collected. This finding is evident despite numerous resources and frameworks for practitioners on how to conduct effective evaluation and increasing pressure from funders to provide evidence of program effectiveness. We identify several organisational, evaluation capacity and knowledge translation factors which contribute to the limited collection of some types of data. In addition, we offer strategies for improving health promotion program evaluation and we identify collaboration of a range of stakeholders as a critical enabler for improved program evaluation. SummaryEvaluation of health promotion programs does occur and resources for how to conduct evaluation are readily available to practitioners. For the purposes of program development, multi-level strategies involving multiple stakeholders are required to address the organisational, capacity and translational factors that affect practitioners’ ability to undertake adequate evaluation.